Generalized Basaloid Follicular Hamartoma Syndrome: A Case Report and Review of the Literature. (March 2015) - Gumaste, Priyanka; Ortiz, Arisa E.; Patel, Amit; Baron, Jonathan; Harris, Ronald; Barr, Ronald
Abstract : Abstract: Basaloid follicular hamartoma (BFH) is a rare, generally benign lesion of importance because of its clinical and histopathological similarity to infundibulocystic basal cell carcinoma. Autosomal dominant generalized BFH syndrome is 1 of the 5 clinical forms of BFH that has been described in the literature. We report a case of BFH syndrome in a 47-year-old Hispanic female who presented with an increasing number of small 1- to 2-mm tan to brown smooth facial papules, few palmar pits, and cobblestoning of the tongue. Her mother had similar lesions on her face. A biopsy of one of the patient's facial lesions confirmed the diagnosis of BFH. Of note, this patient later presented with rapid growth of one of her facial lesions, and a subsequent biopsy confirmed the development of a basal cell carcinoma arising within one of her BFH lesions. Although BFH is classically stable for years and does not require immediate surgical removal, our case highlights the importance of continual monitoring of these patients, given the potential for malignant transformation of these lesions.